Political Orientation Of Dayak Siang Society In The Election Of A Head Of Sub-District In Saripoi Sub-District Murung Raya, Central Kalimantan - Novalia Kristin Anjellina; Setia Budhi; Jamaluddin Jamaluddin; Andi Tenri Sompa; Budi Suryadi (International Journal of Politic, Public Policy and Environmental Issues, 2021)
This study aims to determine the political orientation of the Dayak Siang community in giving their voting rights in the Regional Head General Election in Saripoi Sub-district , Murung Raya Regency, Central Kalimantan. This research is qualitative research with a descriptive approach type. The data collection techniques used by the author are interviews, observation and documentation, data analysis techniques use data reduction, data presentation and drawing conclusions or data verification. Political orientation is a pattern of community behavior which later becomes a culture in certain individuals and communities in state life, Almond and Verba (1984) clarify political orientation into 3 (three) parts, namely cognitive, affective and evaluative political orientation. Research on the orientation of the Dayak Siang community in regional head elections in Saripoi Sub-district is in accordance with the Almond and Verba theory regarding the three components of political orientation of an individual or community group in viewing politics, but the three components of political orientation in Saripoi Sub-district lead to Parochial political culture, the role of government, Village heads and parents influence decision-making by voters in determining their voting rights in the implementation of the Regional General Election.